2015
DOI: 10.1371/journal.pone.0120654
|View full text |Cite
|
Sign up to set email alerts
|

MTHFR 677C>T Polymorphism and the Risk of Breast Cancer: Evidence from an Original Study and Pooled Data for 28031 Cases and 31880 Controls

Abstract: BackgroundMethylenetetrahydrofolate reductase (MTHFR) acts at an important metabolic point in the regulation of cellular methylation reaction. It assists in the conversion of 5, 10-methylenetetrahydrofolate to 5-methyltetrahydrofolate. The latter aids in remethylation of homocysteine to de novo methionine that is required for DNA synthesis. The objective of this study was to examine the effect of MTHFR 677 C>T polymorphism on the risk of breast cancer in the Indian sub-continent.Methods and ResultsWe genotyped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 75 publications
4
11
0
Order By: Relevance
“…The results of our meta-analysis corroborated with other meta-analyses (Yu and Chen 2012;Liang et al 2013;Castro-Quezada et al 2014); (Li et al 2014a;Rai 2014;Pooja et al 2015;Kumar et al 2015) in showing MTHFR C677T as a risk factor for breast cancer. The null association of MTR A2756G in random effects model and an inverse association with breast cancer in Caucasians were consistent with the meta-analysis of Zhong et al (2013).…”
Section: Discussionsupporting
confidence: 91%
“…The results of our meta-analysis corroborated with other meta-analyses (Yu and Chen 2012;Liang et al 2013;Castro-Quezada et al 2014); (Li et al 2014a;Rai 2014;Pooja et al 2015;Kumar et al 2015) in showing MTHFR C677T as a risk factor for breast cancer. The null association of MTR A2756G in random effects model and an inverse association with breast cancer in Caucasians were consistent with the meta-analysis of Zhong et al (2013).…”
Section: Discussionsupporting
confidence: 91%
“…It was found that the 677C>T polymorphism is strongly associated with breast cancer in the East Asian populations [22]. Therefore, our results seem to be more relevant to other population studies: the lack of association of the MTHFR polymorphisms with the breast cancer risk was observed in Indian women [23] and in the residents of Scotland [13], Finland [24] and Greece [25].…”
Section: Resultssupporting
confidence: 60%
“…Then full texts were reviewed and 2 articles (only cases) were further excluded. Based on the inclusion and exclusion criteria, finally, seventy one studies were included in the present met-analysis ( Kakkoura et al, 2015 , Lin et al, 2015 , López-Cortés et al, 2015 , Lu et al, 2015 , Singh et al, 2015 , He et al, 2014 , Huang et al, 2014 , Jiang-Hua et al, 2014 , Wang et al, 2014 , Weiwei et al, 2014 , Liu et al, 2013 , Ozen et al, 2013 , Akram et al, 2012 , Barbosa Rde et al, 2012 , Diakite et al, 2012 , Jakubowska et al, 2012 , Lajin et al, 2012 , Wu et al, 2012 , Batschauer et al, 2011 , Cerne et al, 2011 , Hosseini et al, 2011 , Hua et al, 2011 , Naushad et al, 2011 , Prasad and Wilkhoo, 2011 , Alshatwi, 2010 , Bentley et al, 2010 , Sangrajrang et al, 2010 , Vainer et al, 2010 , Wu et al, 2010 , Cam et al, 2009 , Ericson et al, 2009 , Gao et al, 2009 , Hennquez-Hernandez et al, 2009 , Jin et al, 2009 , Li and Chen, 2009 , Ma et al, 2009a , Ma et al, 2009b , Maruti et al, 2009 , Platek et al, 2009 , Yuan et al, 2009 , Cheng et al, 2008 , Inoue et al, 2008 , Kotsopoulos et al, 2008 , Langsenlehner et al, 2008 , Mir et al, 2008 , Suzuki et al, 2008 , Hekim et al, 2007 , Kan et al, 2007 , Lissowska et al, 2007 , Macis et al, 2007 , Reljic et al, 2007 , Stevens et al, 2007 ...…”
Section: Resultsmentioning
confidence: 99%
“…MTHFR gene T allele has been widely studied as a possible low-penetrance susceptibility allele for a variety of cancers, and in particular, BC. Several studies reported significant association between C677T polymorphism and BC risk ( Kakkoura et al, 2015 , Lu et al, 2015 , He et al, 2014 , Weiwei et al, 2014 , Cheng et al, 2008 ), however some other studies have reported no association between BC and C677T polymorphism ( Singh et al, 2015 , Huang et al, 2014 , Wu et al, 2012 , Ma et al, 2009a , Ma et al, 2009b ). The variation of these results might be induced by difference in ethnicities, sample size, study design and background of patients as well as random error ( Wen et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%